2022
DOI: 10.1007/s40520-022-02290-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of subjective and objective masticatory function among elderly individuals with mild cognitive impairment

Abstract: Background Masticatory function is known to be related to cognitive ability; therefore, factors for improving masticatory function should be identified. Aims This study aimed to identify factors influencing masticatory function associated with mild cognitive impairment (MCI) in elderly individuals. Methods A total of 123 elderly participants [mean age: 76.5 ± 6.5 years; 82 females (66.7%), 41 males (33.3%)] were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The participants were healthy enough from the perspective of physical and mental conditions to manage ADLs and instrumental ADLs [ 26 ]. In addition, they had at least 20 teeth, which is considered a sufficient number of teeth to support masticatory function based on the short arch concept [ 4 , 21 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The participants were healthy enough from the perspective of physical and mental conditions to manage ADLs and instrumental ADLs [ 26 ]. In addition, they had at least 20 teeth, which is considered a sufficient number of teeth to support masticatory function based on the short arch concept [ 4 , 21 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al reported significant associations between MP and the KMMSE score in older individuals [ 21 ]; therefore, a significant multilateral association could be expected among the KMMSE score, MP and ODK. In reality, in Gr3, both the KMMSE score and ODK /ka/ emerged as significant factors associated with MP, and ODK /pa/ showed a more significant association than in Gr2, where ODK /pa/ta/ was distinctively associated with MP (Table 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oral frailty has been associated with an increased risk of new-onset MCI [ 4 ]. Previous studies have revealed that the number of teeth present, occlusal contact area, and maximum bite force are significantly higher in cognitively normal subjects than in impaired subjects [ 5 , 6 ]. Lee et al pointed out that masticatory function measured by the objective mixing ability test was significantly associated with MCI [ 6 ].…”
Section: Introductionmentioning
confidence: 99%